Early age exposure to moisture and mould is related to FeNO at the age of 6 years. Issue 6 (9th May 2021) - Tischer, Christina; Karvonen, Anne M.; Kirjavainen, Pirkka V.; Flexeder, Claudia; Roponen, Marjut; Hyvärinen, Anne; Renz, Harald; Frey, Urs Peter; Fuchs, Oliver; Pekkanen, Juha
Abstract: Background: Exposure to indoor moisture damage and visible mold has been found to be associated with asthma and respiratory symptoms in several questionnaire‐based studies by self‐report. We aimed to define the prospective association between the early life exposure to residential moisture damage or mold and fractional exhaled nitric oxide (FeNO) and lung function parameters as objective markers for airway inflammation and asthma in 6‐year‐old children. Methods: Home inspections were performed in children's homes when infants were on average 5 months old. At age 6 years, data on FeNO (n = 322) as well as lung function (n = 216) measurements were collected. Logistic regression and generalized additive models were used for statistical analyses. Results: Early age major moisture damage and moisture damage or mold in the child's main living areas were significantly associated with increased FeNO levels (>75th percentile) at the age of 6 years (adjusted odds ratios, 95% confidence intervals, aOR (95% CI): 3.10 (1.35‐7.07) and 3.16 (1.43‐6.98), respectively. Effects were more pronounced in those who did not change residential address throughout the study period. For lung function, major structural damage within the whole home was associated with reduced FEV1 and FVC, but not with FEV1/FVC. No association with lung function was observed with early moisture damage or mold in the child's main living areas. Conclusion: These results underline the importance of prevention and remediation efforts of moisture and mold‐damaged buildings in order to avoid harmful effects within the vulnerable phase of the infants and children's immunologic development.